Treatment of a Class I deep bite malocclusion in a periodontally compromised adult - Ferreira Marcelo do Amaral; Ferreira Rogério do Amaral (Sciendo, 2023)
Light forces and an appropriate force system should be used to treat adult patients with periodontal disease.